Correlation of Comorbidities with the Quality of Life Among Pre-Geriatric COVID-19 Survivors in Jakarta Greater Area And Its Review in Islamic Perspective - Annisa Nurul Azrina; RW Susilowati; Muhammad Arsyad (Junior Medical Journal, 2023)
Background: Coronavirus Disease (COVID-19) is a contagious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) that can affect humans. One of the risk factors, such as comorbidities, caused a significant increase in the mortality rate of COVID-19. Health problems arise in accordance with increased human age, resulting in decreased quality of life. Various aspects can influence the quality of life; general quality of life, health, physical, psychological, social, and environmental. In Islam, humans are perceived as the world's leaders; thus, they must preserve their health. This study aims to analyze the correlation of comorbidities with the quality of life in pre-geriatric survivors of COVID-19 in the Jakarta Greater Area and its review according to the Islamic perspective.Methods: This study utilized the correlational analytical survey design with a cross-sectional approach. Samples were obtained by consecutive sampling technique with a total number of 62 respondents. Data collection was done by filling out an online questionnaire distributed in Google Forms. Independent t-tests and Mann-Whitney testing were used to analyze data.Results: There were no significant differences in quality of life in general health from both groups of pre-geriatric COVID-19 survivors, with and without comorbidities and with a p-value 0,005 in each domain.Conclusion: There is no correlation between the quality of life to general health condition, physical, psychological, social, and environmental domains to pre-geriatric COVID-19 survivors in both groups with and without comorbidities.